Observed increasing water constraint on vegetation growth over the last three decades - Jiao, Wenzhe; Wang, Lixin; Smith, William K.; Chang, Qing; Wang, Honglang; D’Odorico, Paolo (Nature communications, 2021)
Despite the growing interest in predicting global and regional trends in vegetation productivity in response to a changing climate, changes in water constraint on vegetation productivity (i.e., water limitations on vegetation growth) remain poorly understood. Here we conduct a comprehensive evaluation of changes in water constraint on vegetation growth in the extratropical Northern Hemisphere between 1982 and 2015. We document a significant increase in vegetation water constraint over this period. Remarkably divergent trends were found with vegetation water deficit areas significantly expanding, and water surplus areas significantly shrinking. The increase in water constraints associated with water deficit was also consistent with a decreasing response time to water scarcity, suggesting a stronger susceptibility of vegetation to drought. We also observed shortened water surplus period for water surplus areas, suggesting a shortened exposure to water surplus associated with humid conditions. These observed changes were found to be attributable to trends in temperature, solar radiation, precipitation, and atmospheric CO 2 . Our findings highlight the need for a more explicit consideration of the influence of water constraints on regional and global vegetation under a warming climate. Jiao et al. conducted a comprehensive evaluation of changes in water constraint on vegetation growth in the extratropical Northern Hemisphere between 1982 and 2015. They document a significant increase in vegetation water constraint over the last three decades.